Treatment of Complicated Henoch-Schönlein Purpura with Mycophenolate Mofetil: A Retrospective Case Series Report. (30th May 2010) - Nikibakhsh, A. A.; Mahmoodzadeh, H.; Karamyyar, M.; Hejazi, S.; Noroozi, M.; Macooie, A. A.; Gholizadeh, A.; Gholizadeh, L.
Abstract : Background . Henoch-Schönlein purpura (HSP) is the most common childhood vasculitis with an incidence of approximately 10 per 100 000 children. There is some evidence to support steroid therapy in the treatment of severe abdominal pain, severe nephritis, and central nervous system involvement. However, the routine use of corticosteroids is controversial. Frequent relapses, lack of response to steroid, steroid dependency, and steroid side effects may occur in some patients. Mycophenolate mofetil (MMF) gains increasing popularity in the treatment of autoimmune disorders, but hitherto, the available evidence to support the use of MMF in HSP is limited to some case study reports. Case Presentation . We report six children with HSP who failed to respond to systemic steroid therapy, whereas MMF successfully treated the manifestations of the disease. Conclusion . The manifestations of HSP disappeared mainly during the first week of treatment with MMF and all the patients were in a complete remission at the end and after discontinuation of the therapy. In our experience, MMF appeared to be safe and effective for the maintenance of remission in the HSP patients.